Characteristics of root resorption in mandibular ameloblastoma using digital radiography - Paputungan, Trisutrisno; Yunus, Barunawaty (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2026)
Objectives: This study aims to provide insights into the characteristics of root resorption associated with ameloblastoma as detected on digital radiography. Review: Root resorption is a pathological process marked by the progressive loss of the root structure, which may result from bacterial infection, traumatic injury, or chemical irritation. Ameloblastoma frequently exhibits distinctive patterns of root resorption, often presenting as blunted or sharply demarcated margins on digital radiographs. Conclusion: Ameloblastoma is known for its high recurrence rate, necessitating comprehensive surgical excision to minimize the likelihood of recurrence. Surgical management often includes the removal of the affected teeth along with the tumor. These treatment decisions are generally guided by histopathological confirmation through incisional biopsy, as several lesions can mimic ameloblastoma despite characteristic radiographic findings such as root resorption.